DESIGN AND DEVELOPMENT OF NOISE SUPPRESSION SYSTEM FOR DOMESTIC GENERATORS - Umar Hammad; Ahmad Aizaz; Abid Ali Khan; Taimur Qurehi (European Scientific Journal, ESJ, 2014)
Increase in demand for standby power sources and disruption in power supply has increased the use of generators manifold for domestic and industrial consumers leading to objections on their use concerning noise pollution. The work presented here aims to focus on how generator set noise is propagated, controlled and reduced to a limit as defined by domestic laws. The presented work is in fact a feasibility of a simple and effective design of an acoustic enclosure for portable generators aims at reducing the radiated noise. This effort is a multi-disciplinary work that comprises acoustics, heat transfer and material science. Heat generation and requirement of cooling air leads to a heat transfer model with internal forced convection. The design is a balance of noise control and thermal management. Noise generating areas have been identified and conventional passive noise control techniques have been used to control and reduce the noise. Acoustic barriers and insulation are used to control the noise propagation at its transmission path. In the conclusion comparison and results of noise are plotted using sound measuring techniques and devices as well as the thermal profiles of cylinder head are compared with and without canopy.